2018
DOI: 10.1002/bsl.2355
|View full text |Cite
|
Sign up to set email alerts
|

Capital jurors, mental illness, and the unreliability principle: Can capital jurors comprehend and account for evidence of mental illness?

Abstract: Recent U.S. Supreme Court opinions have given rise to the question of whether persons suffering from a severe mental illness should be categorically exempt from the death penalty. This article presents a brief overview of relevant U.S. Supreme Court cases and the empirical evidence relevant to this question. We then present our findings on how actual capital jurors respond to and discuss engaging with evidence of mental illness, as drawn from in-depth interviews collected as part of the Capital Jury Project. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…More generally, this finding suggests that stigma towards individuals with mental illnesses still exists and can impact on decisions that people make about individuals. This is in line with previous research that has shown how merely labelling someone as having a mental illness can negatively impact perceptions of these individuals (e.g., Appelbaum & Scurich, 2014;Pescosolido et al, 1999;Sandys et al, 2018). 2 The authors also ran the full analyses without the inclusion of the 'attitudes towards mental illness' covariate.…”
Section: Witness Competency Reliability and Credibility Ratingssupporting
confidence: 80%
See 2 more Smart Citations
“…More generally, this finding suggests that stigma towards individuals with mental illnesses still exists and can impact on decisions that people make about individuals. This is in line with previous research that has shown how merely labelling someone as having a mental illness can negatively impact perceptions of these individuals (e.g., Appelbaum & Scurich, 2014;Pescosolido et al, 1999;Sandys et al, 2018). 2 The authors also ran the full analyses without the inclusion of the 'attitudes towards mental illness' covariate.…”
Section: Witness Competency Reliability and Credibility Ratingssupporting
confidence: 80%
“…In a review of archival data from court cases, Wolbransky (2011) found that jurors were more likely to assign harsher verdicts and recommend the death penalty to individuals who were described as mentally, or emotionally, "disturbed". Thus, when deliberating guilt, the defendant's diagnosis could be viewed as an aggravating factor, which increases culpability for the crime committed (Berryessa et al, 2015;Sandys et al, 2018).…”
Section: Mental Illness and Decision-making In Courtmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, experimental work has generally established that social or genetic disadvantages can indeed attenuate support for capital punishment to varying degrees. For example, the mitigating effects of evidence on certain social disadvantages, such as abuse or history of poverty, have been weak or mixed with regard to affecting support for capital and other types of sentencing (Barnett et al., 2007; Berryessa, 2021; Tetterton & Brodsky, 2007; Monterosso et al., 2005; Najdowski et al., 2009; Stevenson et al., 2010), while some types of natural disadvantages, such as intellectual disability, mental illness, or physical abnormalities, have sometimes, but not always, shown stronger effects on mitigation support (Barnett et al., 2004; Berryessa, 2017, 2020; Boots et al., 2003; Edens et al., 2005; Greene & Cahill, 2012; Najdowski et al., 2009; Saks et al., 2014; Sandys et al., 2018). Yet other studies, and particularly those presenting an offender's genetic disadvantages, have shown little significant mitigating effects to death penalty sentencing (Appelbaum & Scurich, 2014; Appelbaum et al., 2015).…”
Section: Introductionmentioning
confidence: 99%